Dorian para além do retrato : representações na segunda tópica de Freud em O Retrato de Dorian Gray - Pedrosa, Jéssica Nayara Cruz (2018)
The current study had as main objective to analyse the representations of Freud's second topography of mind in The Picture of Dorian Gray. A methodological analysis of psychoanalysis was carried out as a literary critic in Freud, chronologically, from the incursions of the author himself undertaken during the construction of psychoanalytic theory. From this, under a hermeneutical bias, psychoanalytic criticism was discussed and the nineteenth century was studied as a scenario for the transformations of the Self and the implication thereof for the emergence of psychoanalysis and for the publication of Oscar Wilde's novel. From the results found, through the correlation of the characters of Dorian Gray, as the Ego, of Lord Henry, as the Id, and of Basil Hallward, as the Superego, with the formation and maintenance of the psyche of the subject, it was found that the text constitutes an unconscious formation that allows the reader to interpret latent contents from his own unconscious, culminating in representations that, although partial, reiterate the sublimation character of the artistic work not only for the creator, but for the one who appreciates it from a dynamic point of view. Keywords: literature; psychoanalysis; unconscious of the text; second topography; dorian gray.